2011
DOI: 10.1089/jmf.2010.0302
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea, Phytic Acid, and Inositol in Combination Reduced the Incidence of Azoxymethane-Induced Colon Tumors in Fisher 344 Male Rats

Abstract: Experimental as well as epidemiologic studies in human populations provide evidence that consumption of phytochemicals reduces the incidence of degenerative diseases. Green tea (GT) catechins are known for their antioxidative potential. Phytic acid (PA) also acts as a natural antioxidant and may have numerous health benefits. This experiment was designed to investigate the inhibitory effects of combinations of 1% and 2% GT, PA, and inositol (I) in reducing the incidence of azoxymethane-induced colon tumors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…As a popular drink favoured by Asians, in particular Chinese, green tea has received much global attention for its promotion of human health. A number of studies have shown that green tea possesses a wide range of biological activities [3], including antioxidant activity [49], anti-inflammatory activity [10], antimutagenic as well as anticarcinogenic activities [1114], and neuroprotective effects [15]. The major functional constituents of green tea, catechins, account for 8–15% of the dry leaf weight [16].…”
Section: Introductionmentioning
confidence: 99%
“…As a popular drink favoured by Asians, in particular Chinese, green tea has received much global attention for its promotion of human health. A number of studies have shown that green tea possesses a wide range of biological activities [3], including antioxidant activity [49], anti-inflammatory activity [10], antimutagenic as well as anticarcinogenic activities [1114], and neuroprotective effects [15]. The major functional constituents of green tea, catechins, account for 8–15% of the dry leaf weight [16].…”
Section: Introductionmentioning
confidence: 99%
“…This scheme has been studied using the Fenton reagent in vitro in homogenates of large intestinal mucosa from Wistar rats [5].…”
Section: Controlmentioning
confidence: 99%
“…For example, a combination of green tea with phytic acid and inositol (all 2% in drinking water) enhanced the anticancer activity of green tea against colorectal cancer in azoxymethane-treated rats after 41 weeks. 112 Combination with folic acid treatment could also increase the anticancer activity of EGCG against gastrointestinal cancer in vivo. For example, EGCG (12.5 mg/day) combined with folic acid (1 mg/day) for 28 weeks was shown to significantly decrease the number of rats with N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG)-induced gastrointestinal tumors compared to controls or single treatments (p 5 0.011, compared to control).…”
Section: Laboratory Animal Model Studiesmentioning
confidence: 99%